Clinical and neuropathological picture of familial encephalopathy with bifunctional protein deficiency - Paprocka, Justyna; Jamroz, Ewa; Adamek, Dariusz; Stradomska, Teresa Joanna; Głuszkiewicz, Ewa; Grzybowska-Chlebowczyk, Urszula; Marszał, Elżbieta (Folia Neuropathologica, 2007)
Peroxisomal diseases are a heterogeneous group of genetic metabolic disorders which are caused by incorrect biogenesis of peroxisomes or a defect in activity of particular enzymes located in those organelles. D-bifunctional protein (D-BP) deficiency belongs to the second group of peroxisomal diseases characterised by dysfunction of a single peroxisomal enzyme. Bifunctional protein is a catalyst in the second and third stage of the β-oxidation of fatty acids. Gene locus of bifunctional protein deficiency comprises chromosomes 5q2 and 3p23-p22. The authors present two siblings with progressing family encephalopathy. In the younger brother the diagnosis of a bifunctional protein deficiency was made. The girl died before a diagnosis was made; however, due to the presence of a very similar clinical condition a suspicion arises that the girl had a peroxisomal disease. In the siblings were ascertained characteristic dysmorphic features, delayed psychomotor development, polymorphic epileptic seizures and generalized muscular hypotonia with areflexia. The neuropathological findings were consistent in general with MRI findings showing features of hypomyelination. Also neuron heterotopias that were found in autopsy are a form of pathology typical for D-BP.